TRANSITIVITY IN BARRACK OBAMA’S SPEECHES - Henny Fauziah Harahap; Sumarsih Sumarsih (State University of Medan, 2012)
Abstract The objectives of this research were to find out the types of processes, participants, and circumstances, the dominant types of processes, participants and circumstances, and the implication of the dominant process, participant and circumstance in Barrack Obama’s speeches. It was a descriptive quantitative design. The analysis was based on two speeches of Barrack Obama, they were Election Night Victory Speech (November 4th, 2008) in Grant Park, Chicago, Illionis and Obama Inaugural Address (January 20th, 2009) in Washington DC and there were 525 processes, 618 participants, and 204 circumstances in 525 clauses. The result showed the most dominant process was Material process (54,6%), the most dominant of participant was Actor (31,1%), and the most dominant of circumstance was (46,1%). Material Process is the most dominant process because it indicates activities that happen in the outside world of human beings. Furthermore, the speeches of Barrack Obama told about many activities that can be done to make America better. So, the physical or action verbs are mostly used as the representation of the physical experience of human beings. As the process controls the participant so the most dominant participant which appeared in the analysis was Actor. And the last, the most dominant circumstance appeared in this analysis was Location. It was caused Obama mentioned more both place and time in his speeches as the implication of the most dominant process, participant, and circumstance. Keywords: Speech; transitivity